Tradução e adaptação transcultural do Pediatric Visually Induced Dizziness Questionnaire (PVID) para o português brasileiro - Titara, Lilian Maria Bessa de Albuquerque (2021)
Dizziness is the sensation of disturbed or impaired spatial orientation, with no illusion of bodily movement (SALMITO et al., 2020). The term visually induced dizziness refers to dizziness or instability triggered by a complex, distorted and broad visual stimulus, including the relative movement of the visual environment associated with body movement. In this sense, this project proposes to carry out the cross-cultural translation and adaptation of the questionnaire “Pediatric Visually Induced Dizziness Questionnaire”- (PVID) applied to children aged 6 to 17 years old, which quantifies the presence and severity of visually induced dizziness (VID). In this process, the methodology consisted of the following steps, based on Beaton et al. (2007): initially, we searched the literature for validated questionnaires aimed at investigating visually induced dizziness in children in use in Brazil and it was found that there were none; then, two qualified translators, native to the target language and fluent in the source language and culture, translated the test independently, considering conceptual equivalence and avoiding literal translation. Next, a synthesis of the translations was performed. This was done by consensus, by the same committee selected in the procedure mentioned above. This committee built a single version from the comparison of translations and the assessment of semantic, idiomatic, conceptual, linguistic and contextual discrepancies. The next step was the back-translation performed by three collaborators born in the language of the original instrument's language. From the three translations performed, the back-translations were synthesized and the pre-final version of the instrument was built for the original language version performed by three back-translators fluent in Brazilian Portuguese. From there, the final synthesis of the back-translations was carried out and the final version of the translation was prepared, which was submitted for evaluation by a committee of expert judges. Finally, the instrument was applied to 30 children from different social strata and an analysis of the responses was carried out. The committee of judges was composed of fifteen collaborators, most of them specialists in the health area, including otolaryngologists, a speech therapist with expertise in the area of audiology with expertise in the area of dizziness and two pedagogues who opined on semantic adjustments for better understanding of the questions and answers. The authors of the new version included illustrative drawings in order to make the questionnaire items easier to understand and obtain more reliable anwers. After following all the methodological steps, the translation and adaptation of the PVID to Brazilian Portuguese was completed, being able to follow the validation step.